Quality of in-hospital cardiac arrest calls: a prospective observational study. Issue 3 (23rd December 2011) - Akhtar, Naheed; Field, Richard A; Greenwood, Liz; Davies, Robin P; Woolley, Sarah; Cooke, Matthew W; Perkins, Gavin D
Abstract : Objective: To determine the quality and diagnostic accuracy of in-hospital adult clinical emergency calls. Design: Prospective observational study. Setting: Three National Health Service acute hospitals in England. Participants: Adult patients sustaining an in-hospital cardiac arrest (CA) or medical emergency (ME) which required activation of the hospital resuscitation team between 1 December 2009 and 30 April 2010. Main outcome measures: Emergency call duration, emergency team dispatch time, diagnostic accuracy of emergency call (sensitivity/specificity), thematic analysis of emergency call, patient outcomes (return of spontaneous circulation and survival to hospital discharge). Results: There were 426 adult resuscitation team activations. There was variability in emergency call duration ranging from 6 to 92 s (median 15 s; IQR 12–19). The sensitivity and specificity of calls for a CA was 91% (86.4–94.6%) and 62% (55.5–68.7%), respectively. Sensitivity did not change with call duration but specificity increased from 38% (25.8–51.0%) for the shortest calls to 82% (69.5–89.6%) for longer calls; p=0.03. The return of spontaneous circulation rate was 38% for calls when the patient was confirmed as in CA upon arrival of the resuscitation team. Survival to hospital discharge rates was higher in patients with shorter call durations (26%) than calls with longer call duration (12%); p=0.028. Five themes emerged identifying reasons for the increased call delay. Conclusion: There is variability in duration and diagnostic accuracy of in-hospital emergency calls. This is associated with delayed activation of the emergency response. The attempt to differentiate between ME and CA is a source of confusion. A single clinical emergency response for CA and ME calls may provide a more focused and timely emergency response.